Re-understanding and focusing on normoalbuminuric diabetic kidney disease - An, Na; Wu, Bi-tao; Yang, Yu-wei; Huang, Zheng-hong; Feng, Jia-fu (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) has grown up to be an important issue of global public health because of its high incidence rate. About 25% of DM patients can develop diabetic foot/ulcers (DF/DFU). Diabetic kidney disease (DKD) is the main cause of end-stage kidney disease (ESKD). DF/DFU and DKD are serious complications of DM. Therefore, early diagnosis and timely prevention and treatment of DF/DFU and DKD are essential for the progress of DM. The clinical diagnosis and staging of DKD are mostly based on the urinary albumin excretion rate (UAER) and EGFR. However, clinically, DKD patients show normoalbuminuric diabetic kidney disease (NADKD) instead of clinical proteinuria. The old NADKD concept is no longer suitable and should be updated accordingly with the redefinition of normal proteinuria by NKF/FDA. Based on the relevant guidelines of DM and CKD and combined with the current situation of clinical research, the review described NADKD from the aspects of epidemiology, pathological mechanism, clinical characteristics, biomarkers, disease diagnosis, and the relationship with DF/DFU to arouse the new understanding of NADKD in the medical profession and pay attention to it.